Intervensi Masalah Kesehatan Remaja Sekolah di SMA Islam YMI Wonopringgo Kabupaten Pekalongan - Pratiwi, Farah Angelina; Arrohmah, Any Ayu; Nur’aini, Fadhilla Annisa; Amalia, Nadzifa Ziada; Rahmawati, Nur Fitri; Firmansyah, Rifki Andre; Maulana, Jaya (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Adolescent groups demonstrate high vulnerability to various health problems. Based on data obtained from YMI Wonopringgo High School, several health issues were identified related to low knowledge and understanding of health matters, particularly regarding Clean and Healthy Living Behavior (PHBS), Reproductive Health, and Mental Health. Socialization and education programs were designed to enhance students' knowledge and awareness as solutions to the identified health problems. The community service method was implemented through two stages: the first stage involved problem identification, and the second stage involved problem intervention through six programs: Drug Abuse Hazard Socialization (BERANI), Reproductive Health Socialization (Personal Hygiene Genitalia), Mental Health Socialization (Talk It Out), Environmental Cleanliness Activities (Giat Berlian), Hand Washing with Soap Socialization (CTPS), and Anti-Smoking Expo (EAR). Program results showed an 80% increase in participants' knowledge and awareness, along with active participation in health-related question-and-answer sessions, although barriers remained in the form of low participation rates, limited supporting facilities, and challenges in disseminating adequate information regarding other health aspects. The intervention program successfully enhanced adolescents' understanding of health importance and is expected to provide long-term impacts including reduced drug abuse rates, improved adolescent reproductive and mental health, and the creation of healthy, clean, and comfortable school environments.